The impact of maternal factors on neonatal mortality among low birth weight in Aceh Province, Indonesia. - , Satrinawati, Rosnah Sutan (Universiti Kebangsaan Malaysia, 2014)
The health of newborns is inextricably linked to that of their mothers. Some maternal factors can influence neonatal survival, particularly for low birth weight babies who are more vulnerable to diseases than normal weight babies. The aim of this study is to assess the impact of maternal factors onneonatal mortality among low birth weight babies in Aceh Province,Indonesia.Study design was unmatched case control. Data collected from 2010 to 2012 in 8 districts in Aceh province, Indonesia. Total sample was 500, divided into 250 LBW who died in neonatal period (case group) and 250 who did not die in neonatal period (control group). There were 6 maternal variables analysed.Three of six variables analysed were not associated with neonatal mortality among LBW (P > 0.05); these were: maternal death, parity and education level. The age of the mother had a significant association with neonatal mortality among LBW (P < 0.05), but was not a determinant factor. The maternal illness and birth interval were determinant factors of neonatal mortality among LBW(P < 0.05); maternal illness (Adj OR= 2.6; 95 % CI: 1.68 - 4.0) and birth interval (Adj OR= 1.8; 95 % CI: 1.20 - 2.91).Maternal illness and birth interval were determinant factors of neonatal mortality among LBW. Appropriate care throughout stages of pregnancy and increasing women’s knowledge on high risk pregnancy are the key factors to the decrease of the neonatal mortality related to the maternal factors.